SEGI-SEGI PELANGGARAN TERORISME TERHADAP SYARI'AT ISLAM - Ali Musri Semjan Putra (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2015)
One of the methods to prevent terrorism is by explaining to people about its transgression against the teaching of Islam. It is important especially so that the youth can prepare themselves from being exposed to many doctrines that are spread out by the terrorists. It also serves as a beneficial treatment for those who are already influenced by these doctrines. In this paper, I am trying to discuss in details various aspects of transgression of terrorism against the teaching of Islam by analysing the valid evidences from al-Qur’an, Sunnah, and the explanations of prominent and outstanding scholars of Islam.